Micromechanism study on electronic and magnetic properties of silicene regulated by oxygen. Issue 8 (August 2019) - Ding, Li-Ping; Shao, Peng; Yang, Lin-Tai; Sun, Wei Guo; Zhang, Fang-Hui; Lu, Cheng
Abstract: Silicene, a two-dimensional (2D) silicon counterpart of graphene with attractive electronic properties, has attracted increasing attention. Understanding of its interaction with oxygen is of fundamental importance for nano-electronics in silicon-based technology. Here, we have systematically studied the structural, electronic and magnetic properties of silicene with oxygen atoms adsorption by using an unbiased structure search method coupled with First-principles calculations. The results show that the most favorable oxygen adsorption site on silicene surface is bridge site and oxygen atoms tend to chemisorb on silicene. A detailed analysis of the electronic band structure and density of state (DOS) suggests that there is a band gap opening near Fermi level after oxygen adsorption, which lead to pristine silicene changing from a gapless semiconductor to a direct or indirect bandgap semiconductor. The important finding is that two and six oxygen atoms adsorbed silicene are more advantageous due to the relatively large direct band gaps at the K point. The calculated magnetic moments and spin density isosurfaces reveal that the total magnetic moments are mostly localized on silicene sheet. This finding provides new insights for further materials design based on two-dimensional silicon systems.